Juvenile Justice, Technology and Family Separation: A Call to Prioritize Access to Family-Based Telehealth Treatment for Justice-Involved Adolescents' Mental Health and Well-Being - Tolou-Shams, Marina; Bath, Eraka; McPhee, Jeanne; Folk, Johanna B.; Porche, Michelle V.; Fortuna, Lisa R. (Frontiers in Digital Health, 2022)
Separating children from families has deleterious effects on children's mental health and well-being, which is highly relevant for youth in juvenile detention and other out-of-home residential placements. Despite growth in the evidence of family-based interventions in mitigating adverse behavioral health outcomes for justice involved adolescents (JIA), gaps remain in intervention dissemination for JIA; this particularly true for those leveraging digital health technologies, a need that has intensified with the COVID-19 pandemic. Use of digital health technologies for JIAs is pressing to address structural barriers in maintaining JIA-family connections, but also to improve treatment access for detained JIAs. Court systems' capacity to support use of digital health tools, such as telehealth, appear promising. Data on the use of tele-conferencing in U.S. juvenile and family courts were collected from 456 juvenile justice professionals as part of a larger study on judicial decision making. Results suggest overwhelming adoption of video-conferencing for court hearings with only 40% of respondents reporting family court use prior to the onset of COVID-19, but majority (91%) now reporting its routine use. Youth participate from a range of settings, including detention, other residential placement, community-based behavioral health and in-home settings. The COVID-19 pandemic has created a shift in the uptake of video-conferencing platforms that could hold promise for future larger scale use across the juvenile justice system. Findings underscore feasibility and acceptability of technology requirements in key settings that should be leveraged for broad scale implementation of empirically supported family-based interventions to advance behavioral health equity for JIA.